On the integration of one class ofN-dimensional trigonometric series - Kuznetsovci, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove new sufficient conditions for the integrability ofN-dimensional trigonometric series, which follow from unimprovable Sidon-type inequalities.